Social movements and protest - Edwards, Gemma (Key topics in sociology., 2014)
"This lively textbook integrates theory and methodology into the study of social movements, and includes contemporary case studies to engage students and encourage them to apply theories critically. A wide range of protest cases are explored, from American, European and global arenas, including contemporary examples of political violence and terrorism, alter-globalisation, social networking and global activism. Key chapter features encourage students to engage critically with the material: method points uncover the methodology behind the theories, helping students to understand the larger study of social movements; debate points highlight classic arguments in social movement studies, encouraging students to critically assess theoretical approaches; and case studies connect theories to cases, allowing students to relate key principles to real-world examples. A companion website offers additional student and instructor resources, including lecture slides and worksheets"-- Provided by publisher.